Epistemology of Hadith in Ibn ʿArabī's Interpretation of QS. Ar-Raḥmān [55]: 19–20 - Muhammad Syukron Zun-Nurain; Uswatun Hasanah; Nur Fitriyana (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2026)
The study of hadith epistemology in Sufi exegesis represents an important issue in Qur’anic studies. Ibn ʿArabī (d. 638 H), as a prominent Sufi-philosopher, offers an interpretive approach that integrates textual, metaphysical, and intuitive dimensions, yet is often considered subjective and controversial. Therefore, this study aims to examine the epistemology of hadith in Ibn ʿArabī’s isyārī exegesis and the critiques of scholars, particularly regarding his interpretation of QS al-Raḥmān [55]:19–20. This research employs a library study with descriptive-analytical and hermeneutic approaches. The analytical framework combines the theory of isyārī exegesis, Sufi epistemology which places kashf and dhawq as sources of knowledge, and the functional theory of hadith in exegesis, employing Hans-Georg Gadamer’s hermeneutic approach. Data were analyzed through intertextual study of the Qur’anic verse, hadith, and Ibn ʿArabī’s cosmology, as well as basic verification of sanad and matan of the hadith within the framework of taʾwīl. The results show that Ibn ʿArabī understands hadith not only as sources of outward law but also as sources of inner knowledge, revealing metaphysical realities through isyārī, symbolic, dzawqī, and kashfī approaches. Within this framework, hadith function ontologically as a metaphysical foundation for interpretation, epistemologically as a source of maʿrifat, and legitimizes the authority of Sufism in interpreting the Qur’an.